GS263-02+45: A new HI supershell with evidence of having triggered star formation? - Arnal, Edmundo Marcelo (2007)
Aims.We look for galactic neutral hydrogen (Hi) supershells likely to be associated with massive star groupings.Methods.A neutral hydrogen (Hi) line survey carried out at the Instituto Argentino de Radioastronomía (IAR) and the Southern Galactic Plane Survey (SGPS) were the main databases used in this investigation.Results.A new Hi supershell (GS263-02+45) was found in the outer part of the Galaxy. This structure is located at a distance of 5.3 1 kpc from the Sun and has a linear diameter of about 665 40 pc. The expansion velocity of the supershell is ~14 km s. The total amount of atomic gas related to GS263-02+45 is ~2 10 . Based on the analysis of the SGPS Hi data it is concluded that the OB-association Bochum 7 is likely to be interacting with GS263-02+45. This fact together with distance and age arguments may indicate that Bochum 7 was born as a consequence of the evolution of GS263-02+45.